Efficient expression systems for cysteine proteases of malaria parasites: Too good to be true? - Sarduy, Emir Salas (Landes Bioscience, 2013)
Papain-like cysteine proteases of malaria parasites are considered important chemotherapeutic targets or valuable models for the evaluation of drug candidates. Consequently, many of these enzymes have been cloned and expressed in Escherichia coli for their biochemical characterization. However, their expression has been problematic, showing low yield and leading to the formation of insoluble aggregates. Given that highly-productive expression systems are required for the high-throughput evaluation of inhibitors, we analyzed the existing expression systems to identify the causes of such apparent issues. We found that significant divergences in codon and nucleotide composition from host genes are the most probable cause of expression failure, and propose several strategies to overcome these limitations. Finally we predict that yeast hosts Saccharomyces cerevisiae and Pichia pastoris may be better suited than E. coli for the efficient expression of plasmodial genes, presumably leading to soluble and active products reproducing structural and functional characteristics of the natural enzymes.